Similar but not same: language barriers and the facet of life faced by the Indonesians as international students in Malaysia - Zakaria, Muhamad Khairul; Saputra, Rocky Harisman; Embong, Abdul Mutalib; Khadim, Kais Amir; Ab Wahab, Noor Azida; Hailan, Salamun; Abdul Kadir, Firdaus Khairi; Munawarah, Junaidah; Abdul-Kadir, Nurul Ashikin; Mohd Nasir, Nur Yuhanis; Abd Kadir, Kasyfullah (International Information and Engineering Technology Association, 2024)
In the realm of global education, Malaysia stands out as a beacon of excellence, offering a plethora of diverse and flexible academic opportunities. It proudly ranks as the 11th preferred educational destination worldwide, with Indonesia emerging as a pivotal contributor to its international student demography. The annual surge in Indonesian student enrolment in Malaysian universities highlights a trend fueled by the allure of competitive tuition fees, geographical closeness, and shared cultural legacies. However, this growing educational exchange is not without its challenges. Indonesian students in Malaysia navigate a complex linguistic landscape, marked by the country's rich tapestry of languages reflective of its pluralistic society. This research meticulously examines the multifaceted linguistic barriers Indonesian students encounter, both within the academic sphere and in their social interactions. Through an extensive electronic survey, this study delves into the intricacies of academic language comprehension, active participation in academic and extracurricular activities, and the broader spectrum of interpersonal communication, peer acceptance, and adaptation to an English-medium educational setting.